ENGLISH TEACHERS' PERCEPTION TOWARD THE NEEDS OF LEARNING MATERIALS DEVELOPMENT FOR VIRTUAL CLASSROOM ACTIVITIES - Syahdan, Syahdan; Herlinawati, Herlinawati; Syaifullah, Syaifullah (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2022)
Learning process amid the Covid-19 pandemic should run consider appropriate learning materials. This research aimed at investigating teachers’ perception toward the needs of learning materials development for virtual classroom activitis amid Covid-19 pandemic. This research used survey design employing English teachers at senior high schools in several districts in Regency of Rokan Hilir, Riau. There were 36 English teachers participated in the study. The instrument of this study was a questionnaire consisted of 32 questions, with 5 open questions and 27 questions using five-likert scale. The questionnaire asked about perception of teachers toward creativities in teaching, development of material, type of material, and online learning activities. To collect the data, the researchers distributed the questionnaire by Google form, with a support from local English teachers association. In the data analysis, the researchers used descriptive statistics, by presenting Mean, Grand Mean, and Standard Deviation. This study found that the English teachers’ agree to the needs of learning materials development for virtual classroom activities as shown in the grand mean and standard deviation, with 4.02 and 0.647 respectively. It meant that their perceptions were in the level of high category. To conclude, the teachers’ perceptions are in the level of high category toward the needs of Learning Materials Development for Virtual Classroom Activities and they can be the predictors to stimulate teachers’ creativity in using online learning materials.